2020
DOI: 10.1111/jfd.13224
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic characterization of Aeromonas salmonicida subsp. masoucida turbot isolate from China

Abstract: Aeromonas salmonicida is a non-motile gram-negative bacterium that is ubiquitous in aquatic environments. Of its five subspecies, A. salmonicida subsp. salmonicida is known as typical A. salmonicida, which is the most often detected subspecies in diseased fish (Daher et al., 2011). It causes severe septicaemia and acute mortality in susceptible salmonid hosts, whereas the subacute or chronic form of the disease is characterized by the furuncles in the musculature (the sign of furunculosis) (Austin & Austin, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, a wide infection caused by A. salmonicida has been reported in different species of fish worldwide, including rainbow trout ( Oncorhynchus mykiss ), Atlantic salmon ( Salmo salar ), arctic char ( Salvelinus alpinus ), brook trout ( Salvelinus fontinalis ), brown trout ( Salmo trutta ), carp ( Cyprinus carpio ), goldfish ( Carassius auratus ), orange‐spotted grouper ( Epinephelus coioiaes ) and sablefish ( Anoplopoma fimbria ) from Canada, USA, Switzerland, Norway, France, South Korea, Spain, Chile, China and so on (Bartkova et al, 2010; Charette et al, 2012; Evenberg et al, 1986; Huang, Qi, Zuo, Alias, & Xu, 2020; Humphrey & Ashburner, 1993; Pylkkö et al, 2005; Valderrama et al, 2019; Vasquez et al, 2020). In particular, it is worth noting that, more and more studies in China on infection (Lian et al, 2020; Meng et al, 2020; Wang et al, 2020), pathogenicity (Chen et al, 2022; Meng et al, 2017; Yi et al, 2022) and interaction with hosts of A. salmonicida (Huang, Qi, Zuo, Alias, & Xu, 2020; Long et al, 2015; Xia et al, 2022; Xue et al, 2021) have been reported in recent years, implying the popularity and importance of this bacterium in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a wide infection caused by A. salmonicida has been reported in different species of fish worldwide, including rainbow trout ( Oncorhynchus mykiss ), Atlantic salmon ( Salmo salar ), arctic char ( Salvelinus alpinus ), brook trout ( Salvelinus fontinalis ), brown trout ( Salmo trutta ), carp ( Cyprinus carpio ), goldfish ( Carassius auratus ), orange‐spotted grouper ( Epinephelus coioiaes ) and sablefish ( Anoplopoma fimbria ) from Canada, USA, Switzerland, Norway, France, South Korea, Spain, Chile, China and so on (Bartkova et al, 2010; Charette et al, 2012; Evenberg et al, 1986; Huang, Qi, Zuo, Alias, & Xu, 2020; Humphrey & Ashburner, 1993; Pylkkö et al, 2005; Valderrama et al, 2019; Vasquez et al, 2020). In particular, it is worth noting that, more and more studies in China on infection (Lian et al, 2020; Meng et al, 2020; Wang et al, 2020), pathogenicity (Chen et al, 2022; Meng et al, 2017; Yi et al, 2022) and interaction with hosts of A. salmonicida (Huang, Qi, Zuo, Alias, & Xu, 2020; Long et al, 2015; Xia et al, 2022; Xue et al, 2021) have been reported in recent years, implying the popularity and importance of this bacterium in China.…”
Section: Introductionmentioning
confidence: 99%
“…. In particular, it is worth noting that, more and more studies in China on infection (Lian et al, 2020;Meng et al, 2020;Wang et al, 2020), pathogenicity (Chen et al, 2022;Meng et al, 2017;Yi et al, 2022) and interaction with hosts of A. salmonicida (Huang, Qi, Zuo, Alias, & Xu, 2020;Long et al, 2015;Xia et al, 2022;Xue et al, 2021) have been reported in recent years, implying the popularity and importance of this bacterium in China.…”
mentioning
confidence: 99%
“…A. salmonicida affects mainly salmonid species, among which the Atlantic salmon ( Salmo salar ) is considered the most susceptible species [ 10 , 11 , 12 ]. Nonetheless, A. salmonicida has been shown to infect many other fish species, both in freshwater and marine environments [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the farmed turbot ( Scophthalmus maximus ) is mainly threatened by the bacterial pathogens (e.g., the Edwardsiella piscicida (previously known as Edwardsiella tarda ) [8] and Aeromonas salmonicida [9] ), causing an enormous economic loss in this industry. To avoid the antibiotics resistant, and develop an effective immuno-therapy to prevent the diseases is urgent.…”
Section: Introductionmentioning
confidence: 99%